Challenges of Applying Artificial Intelligence in Libyan Higher Education - Singh, Sahibdeep; Bhathal, Gurjit Singh (Journal of Research in Vocational Education, 2025)
This study examines the challenges associated with employing artificial intelligence AI in Libyan higher education. The research identifies significant obstacles, including weak educational policies, inadequate digital infrastructure, and high implementation costs. The study surveyed 314 faculty members from various Libyan universities, revealing that these challenges impede the effective use of AI in education. The findings suggest that addressing these issues is crucial for leveraging AIs potential in improving educational outcomes. The study concluded that the most prominent challenges in employing artificial intelligence in higher education are the high financial costs of implementing AI programs in these institutions The study concludes with recommendations for enhancing digital infrastructure and training human resources to overcome these challenges.